Nilai Pembinaan Karakter dan Moral dalam Novel Dendam Si Yatim Piatu Karya Sintha Rose - Karsiti Karsiti; Restoeningroem Restoeningroem (Universitas Indraprasta PGRI, 2021)
This study aims to describe and explain the values of character and moral development contained in the novel “Dendam” Si Yatim Piatu by Sintha Rose. The sample in this study is the novel